Effects of dietary vitamin C and E supplementation on exercise-induced muscle damage among young weightlifters - Mohammed, Sawash M. (2011)
Dietary supplements vitamin C and E have shown to reduce oxidative stress and muscle damage markers following the exercise. Therefore, it has been hypothesized that markers of oxidative stress and muscle damage induced weightlifting training could be decreased by supplementing subjects with vitamin C and E. 32 trained weightlifters recruited and randomly assigned into two groups: Supplement group were given 500 mg of vitamin C and 400 IU of vitamin E per day, while placebo group given maltodextrine, zero calorie per day for 6 weeks. Serum creatine kinase (CK), lactate dehydrogenase (LDH), aspartate aminotransferase (AST), Alanine transaminase (ALT), creatinine and urea. Urinary TBARS and Circumferences of mid arm, mid-thigh and calf were measured before and after supplementation. All data were expressed as median and interquartile range. All the statistical significance was accepted at p < 0.05. There was no significant effect (p>0.05) of vitamin supplementation on LDH, CK and urinary TBARS between two groups. There was no significant effect of vitamin C and E supplements on hepatic enzymes AST and ALT; there was statistically significant difference (p<0.05) in renal enzymes, creatinine and urea, but no effect happened and the values were within the normal reference value. These data indicate that vitamin C and E were not effective in ameliorating markers of muscle damage and oxidative stress induced weightlifting training in trained individuals. Moreover, intake of vitamin C and E for 6 weeks showed no toxic effects on hepatic and renal function.